How to Film Together. Transtemporalities and Variations of the Extensive in the Cinema of Llinás and Campusano (Anclajes, 2022)
The article aims to investigate the problem of long duration in contemporary Argentinean cinema, based on the cases of La flor (Mariano Llinás, 2018) and Fantasmas de la ruta (José Celestino Campusano, 2013). These are two particularly long films, in which extension, as a creative principle, is articulated with productive strategies, formal endeavors and new spatial constructions. A first dimension of this extension is determined by the productive time. In both works, the duration of the creative processes is linked to the development of long-lasting film communities that depart from conventional funding, production and exhibition procedures. On the other hand, both films intertwine different plots, recomposing genres and narrative structures, as if the length of time became a laboratory of plots that reinvent patterns of verisimilitude and multiply the possibilities of fiction. Finally, there is an expansive impulse that articulates temporal and spatial extensions in both productions, in such a way that the cartographic projection of these long-lasting fictions discovers diverse transtemporal utopias, which in turn correspond to different cinematographic communities and ways of narrating the extension.
Keywords: Mariano Llinás; José Celestino Campusano; Argentine Cinema; temporality; long duration